Inheritance of tomato leaflet acylsugar contents in genotypes derived from an interspecific cross - Gonçalves, Luciano Donizete; Maluf, Wilson Roberto; Cardoso, Maria das Graças; Gomes, Luiz Antônio Augusto; Nascimento, Ildon Rodrigues do (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to determine the inheritance of acylsugar contents in tomato genotypes, from the F2 generation of the third backcross of L. esculentum Mill. ’TOM-584’, after the original cross with the wild accession L. pennellii ’LA-716’. Acylsugar contents in tomato leaflets were measured according to a methodology for reducing sugars determination. The data obtained were evaluated with chi-square tests of monogenic hypotheses of inheritance, under different presumed degrees of dominance, and also under genetic models with the maximum likelihood function, in which presence of a major gene and possible polygenes with additive and non additive effects were tested. For the different presumed degrees of dominance (DD) tested in an array between -0.7 and -0.4, the hypotheses of monogenic inheritance could not be rejected, indicating that high acylsugar contents are controlled by a recessive allele in a locus with incomplete dominance. Genetic models tested under the maximum likelihood function also confirmed the hypothesis of monogenic inheritance. Tomato plants with adequate levels of acylsugar-mediated resistance to arthropod pests can be efficiently obtained in backcross populations, derived from the interspecific cross L. esculentum x L. pennellii.